The Attitude of Women on the Manufacturing of the Indonesian Ulama Council of North Sumatra Regarding the Documentary Video of the Polemic of Polygamy in Indonesia: Sharing Heaven on Vice Indonesia's Youtube Channel - Yogo Pamungkas L Tobing; Iskandar Zulkarnain; Nurbani (International Journal of Scientific Multidisciplinary Research, 2024)
This research examines the cognitive, affective and conative responses of women administrators of the North Sumatra Indonesian Ulema Council (MUI) to the documentary video "Polygamy Polemic in Indonesia: Sharing Heaven" on the Vice Indonesia YouTube channel. This research involved non-participatory observation and in-depth interviews. There were six research informants and one triangulation informant. The information received resulted in saturated data. The results showed that the informants negotiated the film's content cognitively and affectively. Although they recognize the legal legitimacy of polygamy, they conatively refuse to engage in polygamous marriages. Apart from that, there are concerns among women administrators of the North Sumatra MUI that this broadcast could create negative stereotypes and position polygamy as an ambiguous law in Islam so that its practice is no longer relevant to carry out